(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this study is to evaluate the knowledge level of breast milk and breastfeeding of health professionals working in primary health care institutions in Malatya.Material and Methods: A Cross-sectional Study’s survey prepared by using the Handbook of Breastfeeding Counseling translated by Child and Adolescent Reproductive Health Branch of the Ministry of Health of Turkey. 778 people were contacted by the interviewers by visiting the primary health care institutions in Malatya city center and districts, directly. All data was evaluated with SPSS 22 software and p0.05 was accepted as statistically significant.Results: The mean age of the participants was 36.15±8.57 years; 77.6% of them were women; 49.1% were working in Family Health Center. It was determined 80.1% of family physicians and 84.5% of midwives / nurses have been consulting about breast milk / breastfeeding in daily practice. When the respondents’ answers to the statements of knowledge about breast milk/breastfeeding counseling were assessed, there was no significant difference between the answers given by the family physicians and midwives/ nurses (p> 0.05). The participants gave wrong answers to 40% of the questions about conditions that require practical support such as insufficient breastmilk and the conditions related to the breasts. Conclusion: In our study we observed that basic subjects were well known by healthcare personnel whereas there is a serious lack of information, especially in daily practice, which should be constantly updated. We think that the training of breastfeeding and breastfeeding counseling should be updated periodically and especially emphasis should be given to new developments and practical information.